2022
DOI: 10.9778/cmajo.20210257
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases and compliance with provincial guidelines for outpatient antibiotic prescription in cases of otitis media and respiratory infections: a population-based study of linked data in Quebec, Canada, 2010–2017

Abstract: A ntimicrobial resistance is of concern to public health authorities worldwide. [1][2][3][4][5] As the frequency of multidrug resistant bacteria increases, with very few new antimicrobials developed, therapeutic options become more limited. This has led the World Health Organization to place antimicrobial resistance among its top 10 list of global health issues. 6 Antimicrobial use, especially inappropriate use, is the main modifiable determinant of resistance because of how it selects resistant strains. 6 Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The findings suggest that the overall adherence to standard treatment guidelines for antibiotic prescribing in terms of drug selection, dosage, and duration in the studied hospital was suboptimal at only 37.9%. The observation of the suboptimal-level adherence rate was congruent with that observed by previous studies in other European countries [ 37 , 38 ], but contrasted with some studies reporting higher levels of antimicrobial treatment guideline adherence rates: 53% observed in Denmark [ 39 ], 56% in the Netherlands [ 40 ], 57% in the Republic of Korea [ 41 ], and 59% in Canada [ 42 ]. In addition, Ekman et al [ 43 ] reported high adherence to treatment guidelines in Nepal in infants.…”
Section: Discussionsupporting
confidence: 88%
“…The findings suggest that the overall adherence to standard treatment guidelines for antibiotic prescribing in terms of drug selection, dosage, and duration in the studied hospital was suboptimal at only 37.9%. The observation of the suboptimal-level adherence rate was congruent with that observed by previous studies in other European countries [ 37 , 38 ], but contrasted with some studies reporting higher levels of antimicrobial treatment guideline adherence rates: 53% observed in Denmark [ 39 ], 56% in the Netherlands [ 40 ], 57% in the Republic of Korea [ 41 ], and 59% in Canada [ 42 ]. In addition, Ekman et al [ 43 ] reported high adherence to treatment guidelines in Nepal in infants.…”
Section: Discussionsupporting
confidence: 88%